2011
DOI: 10.3189/002214311796905631
|View full text |Cite
|
Sign up to set email alerts
|

Multi-decadal retreat of Greenland’s marine-terminating glaciers

Abstract: ABSTRACT. Many marine-terminating glaciers draining the Greenland ice sheet have retreated over the past decade, yet the extent and magnitude of retreat relative to past variability is unknown. We measure changes in front positions of 210 marine-terminating glaciers using Landsat imagery spanning nearly four decades and compare decadal-scale rates of change with earlier observations. We find that 90% of the observed glaciers retreated between 2000 and 2010, approaching 100% in the northwest, with rapid retreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
149
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 28 publications
23
149
1
2
Order By: Relevance
“…Until mid-1996, cumulative D rep-resents a straight line, because its annual value is assumed constant at the 1996 value of 411 Gt yr −1 . The average value of SMB Greenland over the period 1958-1995 is within 2 % of this value (418 Gt yr −1 ), resulting in an estimated pre-1996 cumulative MB (red line) that remains close to 0, in line with previous results of Howat and Eddy (2011). The fact that the estimated 1995 value of D and the 1958-1995 average value of SMB are similar suggests that ice flow in the mid-1990s was well adjusted to the average annual mass input of the previous decades, reminiscent of an ice sheet in approximate balance ).…”
Section: Comparing Mbm and Gracesupporting
confidence: 77%
“…Until mid-1996, cumulative D rep-resents a straight line, because its annual value is assumed constant at the 1996 value of 411 Gt yr −1 . The average value of SMB Greenland over the period 1958-1995 is within 2 % of this value (418 Gt yr −1 ), resulting in an estimated pre-1996 cumulative MB (red line) that remains close to 0, in line with previous results of Howat and Eddy (2011). The fact that the estimated 1995 value of D and the 1958-1995 average value of SMB are similar suggests that ice flow in the mid-1990s was well adjusted to the average annual mass input of the previous decades, reminiscent of an ice sheet in approximate balance ).…”
Section: Comparing Mbm and Gracesupporting
confidence: 77%
“…Ice-ocean interactions are a major control on the evolution of Greenland glaciers 23 and the enhanced intrusion of warm water of sub-tropical origin (Atlantic water) in the glacial fjords is considered to be a leading explanation for the recent acceleration 24 . It has however been suggested that the current acceleration and retreat of these marine-terminating glaciers will decrease in the near future, as the ice sheet will lose contact with the ocean waters because the bed elevation of these glaciers rises above sea level within tens of kilometres of the coast 2,25,26 . Our results show that the submarine bed channels are more widespread, deeper and extend significantly farther inland than previously thought.…”
mentioning
confidence: 99%
“…16), the 107 marine-terminating glaciers are underlaid by fjords that extend on average 67 km below sea level inland, which is 50% longer than for B2013 (Supplementary Table 1) and 300% than for B2001. If these 107 glaciers were to retreat at an average rate of 110 m yr −1 in the coming century, as they have between 2000 and 2012 26 , only 30 of them would disconnect from the ocean by the end of the century. We report 123 marine-terminating glaciers versus 12 in B2001 and 102 in B2013.…”
mentioning
confidence: 99%
“…Variations in basal topography and fjord width have been previously identified as an important control on the dynamic response of glaciers in many regions of the GrIS Howat and Eddy, 2011;McFadden et al, 2011;Thomas et al, 2009;Carr et al, 2017). In this study, the differences between periods of retreat, acceleration, and thinning between floating and grounded-terminus glaciers suggests basal topography may control the time taken for glaciers to return to a point where retreat 5 slows and velocities return to pre-retreat levels.…”
Section: Influence Of Glacier Geometrymentioning
confidence: 70%
“…Enderlin et al, 2013;Howat and Eddy, 2011;Jamieson et al, 2012), and could also explain differences between groundedterminus and floating ice-tongue glaciers (McFadden et al, 2011), as well as individual glacier variability. At Hagen Brae, for example, the ice tongue is confined by, and strongly attached to, its fjord walls, and retreat away from an island pinning point may have reduced back stress on inland grounded ice, and contributed to its acceleration (Joughin et al, 2010).…”
Section: Influence Of Glacier Geometrymentioning
confidence: 99%